(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
In Nigeria most cities are water stressed, none of the cities are having regular water supply. Quality water for human consumption is a primary duty of the government but they have failed. Also, current cost of boreholes installation has increased beyond their capacity due to Naira devaluation in the world market. Water resources management requires constant monitoring in terms of its qualitative-quantitative values. This study presents potential impact of the Project Evaluation and Review Techniques (PERT) mathematical model software development for the supply of domestic well-water treatment plant. After testing software against the values then, the 37days calculated Expected Time (ET) is unreliable because the risk involved in this project is (100 – 34.23) % = 65.77 %. However, a new completing date can be predicted by PERT mathematical model for supply of domestic well-water treatment plant by varying probability of completion to predict new date of completing the plant. Therefore, concerning this research the Initial probability was moved from 34.23% to 90%. By interpolation with 37 days; the new acceptable date was 97.28 days. The risk involved now (100 – 90) % reduced to 10%, a very good comfortable zone for the project. This information has really helped in two ways: for easy computation and decision making in water supply scheme project. This result is useful in industrialization, individuals, housing estate, small and medium scale industries where quality domestic well-water for crops production is a necessity. Hence, it is recommended that, the developed mathematical models performed